Mapping the Trajectories of Women in Astronomy: Influences and Milestones in Talent Development - Gomez-Arizaga, M (SAGE Publications Inc., 2025)
Astronomy is critical for human development, driving technology and innovation, and creating knowledge that allows humanity to understand the universe more fully. Women, however, remain underrepresented in this field. Many women leave the field before becoming established, yet little is known about women who persist and succeed. The purpose of this study was to explore the abilities, experiences, milestones, and individuals that have contributed to women’s talent development along their trajectories in astronomy, in the specific case of Chile. In-depth interviews were conducted with five talented women in astronomy, who have developed their academic and professional careers in Chile. The results show that micro, meso, and macro levels of influence, in conjunction with different time periods, were critical for the participants’ trajectories and have impacted the direction of women’s paths. The astronomers highlight early experiences, mentor support, validation, and gendered experiences as they navigate their own insecurities and develop self-confidence. Implications for the study of talent development in female astronomers are discussed. © 2025 National Association for Gifted Children.